DESIGNING AN ANIMATION VIDEO FOR TEACHING DIRECT INDIRECT SPEECH AT X GRADE - Trikaloka Handayani Putri; Hurriyatur Rosideh (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2021)
Grammar is one of the skills that are difficult for students. Thus, to over come its problem the teacher needs to build fun teaching way to make students enjoy in learning grammar. One of the ways to make learning fun is attractive media. The purpose of this study was to design animation videos as learning media for X grade. In this study, the researcher used Design-Based Research according to Akker et, al theory (2013). While, there are three stages are included: need analysis, designing phase, and assessment phase. The instruments of the research were interviews and questioner. The data from the interview was student's needs, and the data from the questionnaires were expert's evaluation and teacher's assessment. The result of the preliminary research showed that the students needed attractive media for learning grammar especially in reported speech. The product of this study was an animation video for teaching reported speech entitled designing an animation video for teaching direct indirect speech at x grade. The animation video was also completed with some exercises. The final product looked like the following: animation video was an attractive medium for teaching reported speech. The teacher can use the video as a learning medium.